1998
DOI: 10.1210/jcem.83.7.4927
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acids and Insulin Resistance during Pregnancy1

Abstract: The purpose of this study was to determine whether elevation of plasma free fatty acids (FFA) in early pregnancy would cause alterations in insulin-stimulated glucose disposal similar to those occurring in late gestation. Seven glucose-tolerant women underwent 4-h euglycemic hyperinsulinemic (1 mU/kg.min) clamping during the early second trimester of pregnancy (14-17 weeks) on 2 consecutive days, receiving either lipid (Liposyn II; 1.5 mL/min) and heparin (0.4 U/kg.min; L/H) or saline/glycerol (2.25 g/h; S/G) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…Another hypothesis could be that healthy pregnant women at 14-17 weeks of gestation, show an acute elevation of free fatty acids due to insulin resistance and a decrease in glucose oxidation in a dose-dependent manner [42]. Though we cannot know whether first trimester elevation of free fatty acids that contribute to the development of gestational diabetes or the production of hyperglycemic placental molecules such as tumor necrosis factor- α (TNF- α ), resistin, and leptin induces an increase on free fatty acids [43], animal studies have shown that the intentional addition of free fatty acids in pregnant rabbits induce insulin resistance, while their reduction has the contrary effect [44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis could be that healthy pregnant women at 14-17 weeks of gestation, show an acute elevation of free fatty acids due to insulin resistance and a decrease in glucose oxidation in a dose-dependent manner [42]. Though we cannot know whether first trimester elevation of free fatty acids that contribute to the development of gestational diabetes or the production of hyperglycemic placental molecules such as tumor necrosis factor- α (TNF- α ), resistin, and leptin induces an increase on free fatty acids [43], animal studies have shown that the intentional addition of free fatty acids in pregnant rabbits induce insulin resistance, while their reduction has the contrary effect [44, 45].…”
Section: Discussionmentioning
confidence: 99%
“… 44 The contribution of elevated FFA plasma levels to IR is also clearly demonstrated in late-term pregnant women, who commonly develop IR in the presence of increased FFA levels. 46 Clearly, IR and lipotoxicity create a vicious cycle and a proatherogenic profile. 20 , 47 , 48 Mitochondrial dysfunction in obese WAT is also producing lipid metabolites, ultimately contributing to IR.…”
Section: Insulin Resistancementioning
confidence: 99%
“…27 Therefore, we have investigated whether elevations of plasma FFAs in early gestation (when insulin sensitivity is normal) would produce deterioration of insulin sensitivity comparable to that commonly seen in late gestation. 28 Seven healthy pregnant women were studied. Three of the women were lean (body mass index BMI < 27.3) and four were overweight (BMI > 27.3).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%